Molecular characterization and expression analysis of B-cell lymphoma-2 in Trachinotus ovatus and its role in apoptotic process - Cao, Zhenjie; Yang, Xin; Li, Tao; Liu, Zhiru; Li, Pengfei; Zhou, Yongcan; Sun, Yun (Frontiers in Immunology, 2023)
B-cell lymphoma-2 (Bcl-2) is the first identified member of the Bcl-2 family that performs an anti-apoptotic function in mammals. However, its role in teleosts is not fully understood. In this study, Bcl-2 of Trachinotus ovatus (TroBcl2) was cloned, and its role in apoptosis was investigated. The full-length coding sequence of TroBcl2 contains 687 bp and encodes a protein containing 228 amino acids. Four conserved Bcl-2 homology (BH) domains and one invariant “NWGR” motif located in BH1 were identified in TroBcl2. In healthy T. ovatus, TroBcl2 was widely distributed in the eleven tested tissues, and higher expression levels were found in immune-related tissues, such as spleen and head kidney tissues. After stimulation with lipopolysaccharide (LPS), the expression of TroBcl2 in the head kidney, spleen, and liver was significantly upregulated. In addition, subcellular localization analysis revealed that TroBcl2 was localized in both the cytoplasm and nucleus. Functional experiments showed that TroBcl2 inhibited apoptosis, possibly by reducing mitochondrial membrane potential loss, decreasing DNA fragmentation, preventing cytochrome c release into cytoplasm, and reducing the caspase 3 and caspase 9 activations. Moreover, upon LPS stimulation, overexpression of TroBcl2 suppressed the activation of several apoptosis-related genes, such as BOK, caspase-9, caspase-7, caspase-3, cytochrome c, and p53. Furthermore, knockdown of TroBcl2 significantly increased the expression of those apoptosis-related genes. In addition, TroBcl2 overexpression or knockdown induced or inhibited, respectively, the transcription of NF-κB and regulated the expression of genes (such as NF-κB1 and c-Rel) in the NF-κB signaling pathway as well as the expression of the downstream inflammatory cytokine IL-1β. Overall, our study suggested that TroBcl2 performs its conserved anti-apoptotic function via the mitochondrial pathway and may serve as an anti-apoptotic regulator in T. ovatus.